2010
DOI: 10.1063/1.3369282
|View full text |Cite
|
Sign up to set email alerts
|

Bending in VO2-coated microcantilevers suitable for thermally activated actuators

Abstract: The curvature of VO 2-coated silicon microcantilevers was measured as the temperature was cycled through the coating's insulator-to-metal transition ͑IMT͒, which drives the curvature change mainly through the strain generated during this reversible structural transformation. The films were grown by pulsed laser deposition ͑PLD͒ on heated substrates. Cantilever tip displacement was measured for a 130 m long cantilever as the temperature was changed by recording the deflection of a laser beam, and the curvature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
65
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 24 publications
3
65
1
Order By: Relevance
“…The contraction of the VO 2 crystal in the c r direction causes overall contraction of the film in the direction parallel to the substrate as it undergoes the SPT. This contraction can be used to create large bending in bimorph structures, hundreds of times larger than the bending achievable by thermal expansion alone [1], [4].…”
Section: B Vanadium Dioxide (Vo 2 )mentioning
confidence: 99%
See 3 more Smart Citations
“…The contraction of the VO 2 crystal in the c r direction causes overall contraction of the film in the direction parallel to the substrate as it undergoes the SPT. This contraction can be used to create large bending in bimorph structures, hundreds of times larger than the bending achievable by thermal expansion alone [1], [4].…”
Section: B Vanadium Dioxide (Vo 2 )mentioning
confidence: 99%
“…Studies of the IMT in VO 2 nanobeams were done recently [21], [22], and in 2010 it was observed that a VO 2 -coated 350 μm-long single crystal silicon (SCS) cantilevers experienced curvatures over 2000 m −1 when heated across VO 2 's T Tr [1]. Such phenomenon was not a result of the difference in thermal expansion coefficients ( α) between the SCS and VO 2 , since the observed strain was much larger than what could be achieved by this mechanism.…”
Section: B Vanadium Dioxide (Vo 2 )mentioning
confidence: 99%
See 2 more Smart Citations
“…The differential thermal expansion of the two layers causes the strip to bend when heated or cooled. The deliberate construction of a bimetallic strip analogue (BSA) designed to amplify motion produced by a phase transition has recently been demonstrated for VO 2 , which undergoes a thermally induced metal-insulator transition above room temperature, concomitant with a 0.3% volume change in the material 9,10 . Very recently, micro-actuators were also created from this same material, and actuation was observed as a direct result of the phase transition 11 .…”
mentioning
confidence: 99%